ANALISIS PENGARUH WHOLE BODY VIBRATION (WBV) TERHADAP KELUHAN LOW BACK PAIN (LBP) PADA OPERATOR ALAT BERAT DI PT. X - Halisa Kurniati; Rostika Flora; Rico Januar Sitorus (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2019)
Low back pain is a common disease affecting almost all individuals at some point in their life. Low back pain is multifactorial in origin. The cause of increased prevalence of low back pain in populations of professional drivers is often uncertain. The factor reported to be most strongly associated with low back pain are exposure to whole body vibration. Other possible risk factors with weaker or inconsistenst evidence for influencing low back pain are individual factors (age, time of work, body mass index and physical activitity). This research is conducted observasionally with cross sectional design with a large sample of 70 people which selected by purposive sampling. Data collected from accelerometer, questionnaires, observation and interviews. The results of research obtained that exposure whole body vibration suffered by operator is 0,543 m/s2 and complaints of low back pain on a heavy equipment operators at PT. X is 64,3 %. Bivariat analysis showed that there are significant relationship between whole body vibration (p<0,05;95 % CI 0,99-2,99 OR 1,723), age (p<0,05; 95 % CI 1,42-3,77 OR 2,31), time of work (p<0,05; 95 % CI 1,07-7,81 OR 2,89) with low back pain. There was no significant relationship between body mass index (p>0,05; 95 % CI 0,68-1,37 OR 0,969) and physical activity (p>0,05; 95 % CI 0,55-1,14 OR 0,798) to low back pain. This research conclude that there is correlation whole body vibration with complaints of low back pain. Keyword:  whole body vibration, low back pain, operator